2010
DOI: 10.1016/j.ijpara.2010.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Non-archetypal Type II-like and atypical strains of Toxoplasma gondii infecting marsupials of Australia

Abstract: Australia is geographically isolated and possesses a remarkable diversity of wildlife species. Marsupials are highly susceptible to infection with the cosmopolitan parasite Toxoplasma gondii. Of 46 marsupials screened for T. gondii by multilocus PCR-DNA sequencing at polymorphic genes (B1, SAG3, GRA6, GRA7), 12 were PCR-positive; the majority (67%; 9/12) were infected by nonarchetypal Type II-like or atypical strains. Six novel alleles were detected at B1, indicating greater diversity of genotypes than previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 19 publications
1
62
0
Order By: Relevance
“…The archived strains from the three wallabys from Pennsylvania (Dubey and Crutehley, 2008) were classified as clonal Type III. Recently, Parameswaran et al (2010) characterised T. gondii DNA amplified directly from tissues of naturally-infected kangaroos in Australia and reported the presence of both archetypal Types I and II, and non-archetypal lineage alleles among strains circulating in Australian macropods. Of the 13 specimens PCR-positive with the B1 gene, DNA sequencing identified five with the type I allele, two with the type II or III allele, and seven had new alleles; viable T. gondii were not available for further genotyping.…”
Section: Macropodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The archived strains from the three wallabys from Pennsylvania (Dubey and Crutehley, 2008) were classified as clonal Type III. Recently, Parameswaran et al (2010) characterised T. gondii DNA amplified directly from tissues of naturally-infected kangaroos in Australia and reported the presence of both archetypal Types I and II, and non-archetypal lineage alleles among strains circulating in Australian macropods. Of the 13 specimens PCR-positive with the B1 gene, DNA sequencing identified five with the type I allele, two with the type II or III allele, and seven had new alleles; viable T. gondii were not available for further genotyping.…”
Section: Macropodsmentioning
confidence: 99%
“…Of the 13 specimens PCR-positive with the B1 gene, DNA sequencing identified five with the type I allele, two with the type II or III allele, and seven had new alleles; viable T. gondii were not available for further genotyping. Genotyping of two archived strains (one Macropus rufogriseus, one Vombatus ursinus) from tachyzoites grown in cell culture, revealed an atypical genotype (Parameswaran et al, 2010). Moré et al (2010) cultivated viable T. gondii from two macropods (Macropus rufus, Macropus giganteus) that had died in a zoo in Argentina.…”
Section: Macropodsmentioning
confidence: 99%
“…In Europe and North America, Toxoplasma gondii is considered to have a predominantly clonal population structure, with three main clonal lineages, referred to as Types I, II and III, accounting for >85% of strains isolated from humans and domestic animals [59]. However, recent studies of isolates of T. gondii in wildlife from North and South America, as well as Australia have uncovered more biological and genetic diversity [60,61,62]. Although some strains infecting wildlife appear to be recombinant genotypes derived from crosses between the archetypal clonal lineages, others are atypical strains which possess completely novel alleles.…”
Section: Mode Of Reproductionmentioning
confidence: 99%
“…Molecular epidemiological studies of threatened native wildlife in Western Australia have revealed the occurrence of mixed infections with T. gondii and Trypanosoma spp., which may be associated with the decline of Bettongia penicillata [173]. Mixed infections with different genotypes of T. gondii are common in Australian wildlife, but it is not yet known how this influences the virulence of infections [62].…”
Section: Polyparasitismmentioning
confidence: 99%
See 1 more Smart Citation